Students’ Perceptions of Using TikTok Application as a Tool for Learning English Reading - Intan Monica; Rulik Setiani (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
English language education is often hindered by conventional methods that lack interactivity, leading to student burnout when trying to improve their reading skills. This study investigates students’ perceptions of using TikTok as a medium for learning English reading based on cognitive, affective, and conative dimensions. Specifically, this study aims to evaluate the extent to which the short-form video platform contributes to optimizing literacy comprehension, identify the psychological and technical barriers faced by learners, and formulate pedagogical implications for teaching innovation at the university level. This qualitative study involved 8 English Language Education students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using a thematic approach. The findings indicate that, in the cognitive dimension, students rely on audiovisual elements and short texts as digital reading strategies that are more practical than conventional textbooks. In the affective dimension, the use of these platforms proved effective in minimizing anxiety and enhancing psychological comfort through content relevant to personal interests. Meanwhile, on the conative dimension, students’ motivation is evident in their ability to self-regulate by filtering out distractions from entertainment content, as well as in their initiative to use TikTok as a means of continuously developing their independent language skills. Based on the research findings, the combined use of text, images, and sound in short videos has been shown to help students understand the material more easily without experiencing mental fatigue, foster independent learning habits through strategies for retaining educational content, and consistently stimulate the enrichment of contextual vocabulary outside of formal class hours. In conclusion, TikTok has transformed into an effective informal educational ecosystem. These findings suggest that educators should begin integrating digital media innovations as a complement to pedagogical strategies to enhance students’ active engagement in English literacy in the modern era.